THE IMPACT OF BANCO NACIONAL COMERCIO DE TIMOR LESTE (BNCTL) CREDIT TO SMALL ENTERPRISES PERFORMANCE IN MANATUTO, TIMOR LESTE - Pinto, Suzana Da Silva Doutel (Jurnal Ilmiah Mahasiswa FEB, 2013)
Timor Leste is a country located in Southeast Asia, northwest of Australia in the Lesser Sunda Islands at the eastern end of the Indonesian archipelago. Timor Leste has large as large as 14.874 km2 with as 1.176 million population most of them are farmer. Manatuto is one of the districts of Timor Leste, located in the central part of the country. It has a population of 38,580 and an area of 1,706 km2. This research aims to know the impact of BNCTL credit to SME’s performance in Manatuto. BNCTL is the only one bank that exist in that district. This study use primary data and analyzed by linear regression. 96% respondents believe that credit given by BNCTL is needed because it can help their business run very well without capital problems. In addition, 100% of respondent said that the procedure in proposing credit of BNCTL is easy. based on adjusted R2 known that the credit of BNCTL has positive contribution as 95,9%. It caused by the lack of capital that influence to business turnover of Small Enterprise. Then after credit was accepted by Small Enterprise, it could help Small Enterprise to fulfill their capital needs in financing their business cost such as stock, payable and receivable. It proven by questionnaires, that is 40% respondent have income more than $4,000-higher than before which is 0% respondent does not have income as high as it. Furthermore, to show how the importance of credit to Small Enterprise performance is can be seen by the result of empirical panel regression model that: (1) If Small Enterprise in Manatuto do not get credit from BNCTL, it makes the income will be decrease as IDR. -3.994.327.385, Meanwhile, every increasing of credit as IDR.1 will increase the Small Enterprise income as IDR 0.067. In other words, the more higher of credit number is implicated appreciate the Small Enterprise income in Manatuto,Timor Leste.Keywords: Income, Credit, Small Enterprise, BNCTL